Analysis of Students' Self-Confidence in Class XI MIPA Learning at UPT SMAN 1 Gowa - Herman, Magfira; Asfiana, Asfiana; Fadillah, Nurfatin; Ayuningtyas, Herlianty Tri Dimas; Saparuddin, Saparuddin (ARRUS Journal of Mathematics and Applied Science, 2023)
This study uses a descriptive research approach with quantitative methods. It was carried out at UPT SMAN 1 Gowa with a population of XI MIPA student consisting of 8 classes. The research sample consisted of 36 people who were randomly selected. The instrument used was a student self-confidence questionnaire with 30 items, which measured indicators of self-confidence, assertiveness, responsibility, and positive thinking. Attitude data that was originally ordinal in nature was processed using Microsoft Excel with the Successive Interval (MSI) method, turning it into interval data. After processing the data, analysis and classification are carried out based on the percentage of the attitude scale. The results showed that the level of self-confidence of class XI MIPA students at UPT SMAN 1 Gowa as a whole was low. The percentage of the indicator of self-confidence is 66% in the low category, the percentage of the indicator of assertiveness is 67.33% which is also low, the percentage of the indicator of responsibility is 70% which is in the medium category, and the percentage of the indicator of positive thinking is 69% which is also low. Although the indicator of being responsible has the highest percentage, overall all indicators of student self-confidence are in the low category, especially the indicator of self-confidence.